Clinical Observation of Employment of Umbilical Cord Derived Mesenchymal Stem Cell for Juvenile Idiopathic Arthritis Therapy - Liming Wang; Yu Zhang; Hongtao Li; Jingxin Hong; Xiaobo Chen; Ming Li; Wen Bai; Jiangang Wang; Yongjun Liu; Mingyuan Wu (Stem Cells International)
Juvenile idiopathic arthritis (JIA), known as Juvenile rheumatoid arthritis, is the most common type of arthritis in children aged under 17. It may cause sequelae due to lack of effective treatment. The goal of this study is to explore the therapeutic effect of umbilical cord mesenchymal stem cells (UC-MSCs) for JIA. Ten JIA patients were treated with UC-MSCs and received second infusion three months later. Some key values such as 28-joint disease activity score (DAS28), TNF-α, IL-6, and regulatory T cells (Tregs) were evaluated. Data were collected at 3 months and 6 months after first treatment. DAS28 score of 10 patients was between 2.6 and 3.2 at three months after infusion. WBC, ESR, and CRP were significantly decreased while Tregs were remarkably increased and IL-6 and TNF-α were declined. Similar changes of above values were found after 6 months. At the same time, the amount of NSAIDS and steroid usage in patients was reduced. However, no significant changes were found comparing the data from 3 and 6 months. These results suggest that UC-MSCs can reduce inflammatory cytokines, improve immune network effects, adjust immune tolerance, and effectively alleviate the symptoms and they might provide a safe and novel approach for JIA treatment.